Pemanfaatan Tembok Sekolah Dasar sebagai Mural Pendidikan Literasi: Utilization of Elementary School Walls as Literacy Education Murals - Wijayanti, Sri Hapsari; Khaqi, Rizal Bay; Feriyadi, Farhan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
As a form of participation of universities, which are members of LLDIKTI region III, for survivors of the eruption of Mount Semeru in Lumajang, East Java, a thematic community service program (KKNT) "Building the Country" has been held on November 12-25, 2023. One of the targets of the activity is SDN Sumberwuluh 02, Candipuro District, Sumbermujur Village. The school wall has been used as a mural containing educational messages on literacy and cultural literacy to motivate Mount Semeru survivor students to remain enthusiastic about learning and proud of the new environment and culture of the region. The stages of activities include preparation, mural painting activity, and monitoring-evaluation. The mural was completed in three days, involving students, lecturers, and teachers working together. The activity results show that the murals have been well drawn, attractive, and communicative. Combining images, text, and colors in murals with positive messages provides a cheerful atmosphere relevant to students' daily lives without ignoring Lumajang icons. Thus, literacy education murals are suitable for use in the school environment. The school is also helped by the promotion of the school through educational murals.